Etos Kerja Islam: Studi Komparatif pada Karyawan Generasi Y dan Generasi Z - Anissa Lestari Kadiyono; AF Mirza Firmansyah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
Indonesia's Muslim fashion industry is growing rapidly, and the development of its organizational system based on Islamic values and ethics has been a basic guideline for organizational activities. However, the meaning of Islamic work ethics, which is the basis for employees to carry out every activity and influence employees' commitment, participation, and performance, may be different for employees belonging to Generation Z or employees belonging to Generation Y. Employees belonging to Generation Z are known as the instant generation and digital natives. Generation Y employees are known for their focus on personal and individualistic values. This can certainly show behavior with different meanings of Islamic work ethic. This research was conducted on 278 employees from companies that apply Islamic work culture using a quantitative descriptive method and convenience sampling. The data was collected online through Google Form and descriptive analysis was carried out to see the differences in Islamic Work Ethic between Generation Y and Generation Z. The results showed that there is no difference in the Islamic Work Ethic displayed by the employees despite being from different generations. However, there are differences in behavior and understanding of work ethics that can be used as a basis for companies to improve the work ethics of their employees.